GROWTH AND WATER CONSUMPTION OF TWO BEAN SPECIES UNDER IRRIGATION WITH SALINE WATER - BECKMANN-CAVALCANTE, Márkilla Zunete; Lucena CAVALCANTE, Ítalo Herbert; CAVALCANTE, Lourival Ferreira; SOUSA, Gasparino Batista de; SANTOS, João Batista dos; Medeiros de SOUZA, Maria do Socorro (Scientia Agraria, 2008)
Salinity is an important environmental problem, specially in regions where irrigation with low quality water is practiced. In this sense, an experiment was carried out from May 2005 to August 2005 at Federal University of Paraiba, Areia, Brazil aiming to evaluate the growth and water consumption of Phaseolus vulgaris e Vigna unguiculata, irrigated with different salinity levels. The treatments were distributed in a completely randomized design, in factorial arrangement 6 x 2 referring to electrical conductivity levels of water irrigation (ECw), as follows: 0.0; 1.5; 3.0; 4.5; 6.0 e 7.5 dS m-1 and two bean species, respectively, with four repetitions and six pots in each parcel. The stem diameter, shoot and root dry mass and water consumption of bean plants were evaluated. Increasing water salinity level, the results of all variables decreased drastically for both species. Phaseolus vulgaris species is more deleteriously affected by water salinity than Vigna unguiculata.